2005
DOI: 10.3168/jds.s0022-0302(05)72814-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nursing Management and Skeletal Size at Weaning on Puberty, Skeletal Growth Rate, and Milk Production During First Lactation of Dairy Heifers

Abstract: Forty Israeli-Holstein 5-d-old calves were used to determine the effect of increasing calf body weight (BW) and skeletal size during the nursing period on age and skeletal size at puberty and on skeletal size and performance during first lactation. The calves were randomly allotted to 2 experimental groups as follows: milk replacer (MR) [calves were given 0.450 kg/d dry matter of milk replacer for the first 50 d of life] and milk-fed (MF) [calves had free access to milk in two 30-min meals/d]. From weaning to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
117
7
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 17 publications
15
117
7
13
Order By: Relevance
“…Skeletal measurements and body condition score changes suggest that the live weight differences resulted from the enhanced deposition of both lean tissue and fat. Shamay et al (2005) found that differences in skeletal size that occurred during the preweaning phase disappeared post weaning. This observation was supported by results from the current study in which calves offered higher levels of MR were significantly larger in size at weaning, only for these differences to disappear shortly after weaning.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Skeletal measurements and body condition score changes suggest that the live weight differences resulted from the enhanced deposition of both lean tissue and fat. Shamay et al (2005) found that differences in skeletal size that occurred during the preweaning phase disappeared post weaning. This observation was supported by results from the current study in which calves offered higher levels of MR were significantly larger in size at weaning, only for these differences to disappear shortly after weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term effects of pre-weaning nutrition Bar-Peled et al (1997), Shamay et al (2005), Moallem et al (2006) and Drackley et al (2007) all found a positive relationship between level of nutrition in early life and subsequent milk production. Additionally, Shamay et al (2005) reported a 23-day reduction in age at puberty and Bar-Peled et al (1997) demonstrated a 31-day reduction in first-calving age when heifer calves were offered a higher feed level up to weaning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations